(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
The photo-stability of the dye determines the longevity of solid-state dye laser in which it is used. The parameter is often determined by measuring the photo-decay time of dye with conventional fluorescence spectrometer. In the present study the Sol- Gel glasses matrix/ composites were prepared using Sol-Gel technique. Three dyes namely Rhodamine 6 G (Rh-6G), Rhodamine B (Rh-B) and Acrajlavine were doped to prepare these lasing materials. Fluorescence photo-bleaching was measured in dye doped Sol-Gel glasses/composites. The decay of fluorescence signal versus cumulative excitation energy was recorded. These results are explained using a simple model purposed by A. M. Weiss et al.